2010
DOI: 10.1523/jneurosci.3155-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Dynamics Regulate Hsp27-Mediated Rescue of Neuronal Plasticity Deficits in Tau Transgenic Mice

Abstract: Molecular chaperones regulate the aggregation of a number of proteins that pathologically misfold and accumulate in neurodegenerative diseases. Identifying ways to manipulate these proteins in disease models is an area of intense investigation; however, the translation of these results to the mammalian brain has progressed more slowly. In this study, we investigated the ability of one of these chaperones, heat shock protein 27 (Hsp27), to modulate tau dynamics. Recombinant wild-type Hsp27 and a genetically alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 41 publications
1
134
0
Order By: Relevance
“…We used dynamic light scattering (DLS) to assess how the Hsp90/FKBP51 complex was regulating the kinetics of global tau aggregation (44). For these studies, tau aggregation was induced with heparin sulfate in the presence of Hsp90 or FKBP51 alone and in the presence of Hsp90 and FKBP51 together.…”
Section: Fkbp51 Depletion Reduces Tau Levels In Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…We used dynamic light scattering (DLS) to assess how the Hsp90/FKBP51 complex was regulating the kinetics of global tau aggregation (44). For these studies, tau aggregation was induced with heparin sulfate in the presence of Hsp90 or FKBP51 alone and in the presence of Hsp90 and FKBP51 together.…”
Section: Fkbp51 Depletion Reduces Tau Levels In Brainmentioning
confidence: 99%
“…FKBP51 expression was observed in the HPC; however, the AAV did not transduce all neurons ( Figure 4A). Due to this typical limitation of AAV use, a fluorescent masking technique previously developed by our lab was used to evaluate the levels of tau in neurons express- ing the AAV product, in this case FKBP51 or GFP (44). Triple-immunofluorescent staining of sections for FKBP51, total tau, and the neuronal marker, NeuN, revealed that the amount of tau found within FKBP51-positive neurons was significantly increased compared with tau levels in neurons overexpressing GFP (Figure 4, B and C).…”
Section: Fkbp51 Depletion Reduces Tau Levels In Brainmentioning
confidence: 99%
“…Until now, HSPB1, HSPB5, and HSPB8 have been the most widely studied members. They have been found to reduce protein aggregates caused by proteins containing an expanded polyQ tract (HSPB8 [20]), tau (HSPB1 [34][35][36]), amyloid-beta (HSPB1, HSPB5, and HSPB8 [37,38]), TDP43 (HSPB8 [15]) and SOD1 (HSPB1, HSPB5, and HSPB8 [18,39]). However, only little is known about were treated with bortezomib (100 nM) or with 3-MA (20 mM) and wortmannin (200 nM) overnight.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification and Statistical Analyses-Quantification of all blots was performed using ImageJ software as described previously (30). Graphs are plotted based on relative intensity values.…”
Section: Methodsmentioning
confidence: 99%